The Role of Ar-Ridho Islamic Institute in Mualaf Development Study on Mualaf at Ar-Ridho Islamic Institute in Siantan Hilir Village, North Pontianak - Taruna, Taruna; Fatmawati, Fatmawati; Rahmaniah, Ema; Al Mutahar, Hasan; Sudirman, Sudirman (Cita konsultindo, 2025)
The research objectives describe the role of the Ar-Ridho Islamic Institute, the form, material and method of coaching. Descriptive research type with a qualitative approach, collection techniques with observation, interviews and documentation, Informants consisted of 5 informants. The results of the research are well done, orderly and smooth, Mualaf has knowledge, understanding of Islamic religious science in theory and practice in his daily life. The non-physical form of coaching conveys material for understanding Islamic religious knowledge in theory and practice about Akidah, Islamic Sharia, Akhlak, procedures for carrying out worship, ablution, congregational prayer, speech skills and training using the lecture method, Qur'anic and Prophetic stories and the Tarqib and Tarhib method. Physical coaching, sports activities and community service in the Ar-Ridho Islamic Institute environment. The results of coaching can be seen from the coaching strategy, coaching programme, implementation of coaching and its benefits for Mualaf. Suggestions for the management of the Ar-Ridho Islamic Institute to improve facilities, infrastructure and collaborate with stakeholders, coaches (officers) to be more active, innovative in encouraging Mualaf to participate in coaching activities, to Mualaf to be more serious, earnest, and steadfast in gaining knowledge of Islam as an obligation, as well as provisions for themselves in the world and in the hereafter.